Exposure to extrinsic stressors, social defeat or bisphenol A, eliminates sex differences in DNA methyltransferase expression in the amygdala. (1st June 2017) - Wright, E. C.; Johnson, S. A.; Hao, R.; Kowalczyk, A. S.; Greenberg, G. D.; Ordoñes Sanchez, E.; Laman‐Maharg, A.; Trainor, B. C.; Rosenfeld, C. S.
Abstract : Chemical and psychological stressors can exert long lasting changes in brain function and behaviour. Changes in DNA methylation have been shown to be an important mechanism mediating long lasting changes in neural function and behaviour, especially for anxiety‐like or stress responses. In the present study, we examined the effects of either a social or chemical stressor on DNA methyltransferase (DNMT) gene expression in the amygdala, an important brain region modulating stress responses and anxiety. In adult California mice ( Peromyscus californicus ) that were naïve to social defeat, females had higher levels of Dnmt1 expression in punch samples of the central amygdala (CeA) than males. In addition, mice that underwent social defeat stress showed reduced Dnmt1 and Dnmt3a expression in the CeA of females but not males. A second study using more anatomically specific punch samples replicated these effects for Dnmt1 . Perinatal exposure (spanning from periconception through lactation) to bisphenol A or ethinyl oestradiol (oestrogens in birth control pills) also abolished sex differences in Dnmt1 expression in the CeA but not the basolateral amygdala. These findings identify a robust sex difference in Dnmt1 expression in the CeA that is sensitive to both psychological and chemical stressors. Future studies should aim to examine the impact of psychological and chemical stressors on DNA methylation in the CeA and also investigate whether Dnmt1 may have an underappreciated role in plasticity in behaviour.